Ideology and Symbolic Meaning: Critical Discourse Analysis of Gudang Garam International Filter Advertisement - Rameda, Naufal; Irwansyah (Indonesian Scientific Journal (Jurnal Ilmiah Indonesia), 2024)
This research investigates how the Gudang Garam Filter Internasional cigarette ad,